A novel homozygous variant in PADI6 is associate with human cleavage-stage embryonic arrest - Cao, Guangyi; Zhu, Xiangyu; Lin, Yuling; Fang, Junshun; Shen, Xiaoyue; Wang, Shanshan; Kong, Na (Frontiers in Genetics, 2023)
Repeated absence of useable embryos is a difficult problem for infertility patients. Among them, embryonic developmental arrest is more common, but the genetic cause is not known. The embryos of a patient who came to our hospital three times could not develop beyond the four-cell stage. In addition to recording the developmental details of the embryos by daily photo-taking, the PADI6R132C homozygous variants was further confirmed by whole-exome sequencing. Subsequently, PADI6R132C was analyzed by bioinformatics methods for conservativeness across species. In addition, the possible impact of the pathogenic mutation on the structure of the protein PADI6 were also assessed. Generally, we identified a homozygous variants [NM_207421.4, c.394C>T(p.R132C] in the middle protein-arginine deiminase domain in PADI6 gene. The homozygous variant is highly conserved across species. Homozygous variant in PADI6R132C could cause a human cleavage-stage embryonic arrest in female patients. These findings provide further evidence for the important roles of the homozygous PADI6R132C variant in embryonic development. Our findings contribute to a deeper understanding of the molecular genetic basis of female infertility.